Neurovascular hamartoma: a case report of a tongue lesion - Caldeira, Laira; Poli Grecco, Letícia; Petereit Trombeli, Gustavo Henrique; Moço Silva, Marceli; Burgos Ponce, José (Brazilian Journal of Case Reports, 2022)
Hamartoma is a proliferation of normal cells and tissues, which are considered endogenous to the site of injury. Oral neurovascular hamartoma (NVH) presents as exophytic lesions, usually with a smooth surface, and less than 10 mm in diameter. Hamartomas arising in the oral cavity are uncommon and may show a variety of clinical presentations and histological and growth patterns. We present a case of oral neurovascular hamartoma lesion in the tongue of a 47-year-old individual, consisting of nerve bundles and blood vessels. Although rare, the neurovascular hamartoma should be considered in the differential diagnosis of tongue lesions.